(untitled) (Research, Society and Development, 2022)
This research aims to weave a reflection on the normative curricular prescription strategies imposed on schools, in which teachers seek to make visible and make viable existing knowledge, through tactics that subvert and recreate spacetime, privileging the textures of networked knowledge and counter-hegemonic action. The study is an essayistic bet, uses the qualitative method, carried out from bibliographic procedures, as it proposed the reading, analysis and interpretation of articles published in scientific journals, books, theses and dissertations that address the subject. The theoretical basis was the study in/of/with everyday life, starting from the central idea of ​​“everyday life” of the French historian and philosopher Michel de Certeau. The results point to the need to reflect on everyday school life, not just limiting it to the problems of schools and training processes. Therefore, it is necessary that studies aimed at teacher training and curriculum commit and dedicate themselves to the work of/in/with the daily life and its vicissitudes, with a focus on valuing the curricula practiced/lived in/of/with the schools, highlighting the tactics, and the subjective and singular creations of each teacher, always taking into account the tension of a hegemonic education in favor of an emancipatory, multicultural, ethical, plural and inclusive education.